Enteral nutrition and dynamics of citrulline and intestinal fatty acid-binding protein in adult ICU patients. (October 2021) - Padar, Martin; Starkopf, Joel; Starkopf, Liis; Forbes, Alastair; Hiesmayr, Michael; Jakob, Stephan M.; Rooijackers, Olav; Wernerman, Jan; Ojavee, Sven Erik; Reintam Blaser, Annika
Summary: Background and aims: Plasma citrulline and intestinal fatty acid binding protein (I-FABP) are biomarkers reflecting enterocyte function and intestinal mucosal injury. The aim was to describe daily dynamics of citrulline and I-FABP concentrations in association with enteral nutrition (EN) in adult ICU patients. We hypothesized that success or failure of EN is reflected by differences in citrulline and I-FABP levels at admission, as well as in daily dynamics over the first week. Methods: The present study was a planned sub-study of the iSOFA study (ClinicalTrials.gov Identifier: NCT02613000). With delayed informed consent we included adult (18 years or older) patients admitted for unlimited care to 5 ICUs in Europe. Citrulline and I-FABP were assessed and nutritional data recorded daily during the first week of the patients' ICU stay. Results: The study included 224 patients with 693 plasma samples analyzed for citrulline and 695 for I-FABP. The median ICU stay was 2 (IQR 1–4) days and 35 patients (15.6 %) stayed in the ICU for ≥ 7 days. The majority of patients (184/224; 82.1 %) received EN or oral nutrition (ON) during their ICU stay, in 164 patients (73.2 %) nutrition was started within 48 h of admission (early enteral or oral nutrition, EEN/ON). Median biomarker concentrations on admission were: citrulline 24.5 (IQR 18.1–31.7) μmol/L and I-FABP 2763 (1326–4805) pg/mL. Reference range for citrulline was 17–46 μmol/L and for I-FABP 377–2049 pg/mL. Patients with EEN/ON demonstrated an increase in citrulline concentrations over the first week in ICU unlike those not receiving EEN/ON (P = 0.049 for the mean log-citrulline values over time between groups) as well as higher average citrulline concentrations. Success of EEN/ON (80 % of caloric target achieved by day 4) was associated with citrulline values increasing from day 4, whereas a slight decrease was observed with unsuccessful EEN/ON. However, these dynamics over time were not statistically significantly different (P = 0.654). Patients with EEN/ON unexpectedly had I-FABP values higher than those without (average values for all days P = 0.004). Median I-FABP values on day 3 were higher with successful EEN/ON (646 (IQR 313–1116) vs 278 (IQR 190–701) pg/mL, P = 0.022). Conclusions: EEN/ON was associated with higher values and different dynamics of citrulline over the first week in ICU. No clear difference of measured biomarkers was seen when patients were compared according to success of EEN/ON. Our study does not allow suggesting certain thresholds of citrulline nor I-FABP that could be used for bedside decision-making with regard to EN. This study was a planned sub-study of the iSOFA study (ClinicalTrials.gov Identifier: NCT02613000).